PENGARUH INTERVENSI FARMASI TERHADAP KONTROL ASMA DAN KUALITAS HIDUP PADA PASIEN ASMA DI YOGYAKARTA - RUSDI, MESA SUKMADANI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Success in improving the quality of life and asthma control both adult and children with asthma can not be separated from the role of pharmacy in providing information about asthma, recommend the use inhalers properly to the patient, recalling the indications given by doctors and possible side effects (Gonzalez - Martin, 2003; Mehuys, 2008).The purpose of this study was to determine the effect of pharmacist counseling inhalation therapy in patients with persistent asthma toward asthma control and quality of life inasthma patients which scores assessed with Asthma Control Test (ACT) and Asthma Quality of Life Quetionaire ( AQLQ ). The research was conducted by quasi experimental.The study involved 50 patients - men and women aged 17-75 years with a variety of backgrounds education, employment status, long-suffering asthma, comorbidities and severity of asthma.. Sampling was carried out with consencutive sampling method. The subjects were divided into 2 groups randomly, with 25 patients in the counseling group and 25 patients in the control group. Mann-Whitney test on the mean change in scores ACT between the counseling group and the control group differed significantly (p = 0,023 [p < 0,05]). Mann- Whitney results of AQLQ score showed a nonsignificant difference between counseling groups and control groups ( p = 0,081 [p > 0,05] ) either in whole domain, emotional domain (p = 0,692[p < 0,05], environment domains (p = 0,879[ p > 0,05]) and domains of activity (p = 0,119 [ p > 0,05]). But AQLQ score showed a significant difference in health domain (p = 0,011 [ p < 0,05]) . In the Spearman, there was strong correlation (p = 0,000, r = 0,732) and towards a positive correlation between the increase in the average ACT score and AQLQ score. Which means that, the higher the control of asthma patients (asthma control), the quality of life of patients with asthma will increase. Counseling pharmacists have a significant influence on the level of control of persistent asthma patients (p = 0,023 [p <0,05]). But there was no significant effect of intervention farmacist on the level of quality of life of patients asthma with persistent levels (p = 0,081[p >0,05]).